Repair of Bronchial Anastomosis Following Lung Transplantation - Chamogeorgakis, Themistokles; Moquin, Kenneth; Simoff, Michael; Nemeh, Hassan (The Thoracic and Cardiovascular Surgeon, 2021)
Background Bronchial anastomotic complications are reported in 2 to 18% of patients after lung transplantation. The majority of complications can be managed with bronchoscopic intervention. When extensive dehiscence is present, surgical intervention can be entertained.Materials and Methods Between March 1, 2006, and December 31, 2019, our program performed 244 lung transplantations. We conducted a retrospective review of our patient cohort and identified patients who suffered from significant anastomotic complications that required surgical interventions.Results Twenty-eight and 216 patients underwent single and bilateral lung transplantations, respectively. Eighteen patients developed airway complications (7.4%). The incidence of anastomotic complications was 5.2% (24 complications for a total of 460 bronchial anastomoses). Four patients were managed conservatively. The majority of the bronchial anastomotic complications were managed endoscopically (eight patients). Four patients with associated massive air leak underwent repair of the bronchial anastomosis and two patients were retransplanted because they developed severe distal airway stenosis.Conclusion Bronchial anastomotic complications are a major cause of morbidity in lung transplantation. The majority of cases can be managed bronchoscopically. In more severe cases associated with massive air leak or imminent massive hemoptysis from bronchopulmonary arterial fistula, surgical intervention is necessary. Aortic homograft interposition along with vascularized pedicle wrapping may be a viable option to re-establish airway continuity when tension-free bronchial anastomotic revision is not possible. In cases with smaller bronchial defects, primary repair with utilization of a vascularized flap can be effective as treatment option.
Keywords: transplantation; lung; bronchial anastomosis; stent; airway